The Influence of Marketing Mix on the Purchase Decision of Pristine 8.6+ Drinking Water Products in Sidoarjo Regency, East Java - Budi Setyo Utomo; Ignatia Martha Hendrati (Eduvest - Journal of Universal Studies, 2024)
Pristine is a product manufactured by PT. Super Wahana Tehno, which applies high pH drinking water in its composition. This research aims to determine the influence of the marketing mix (4P) on purchasing decisions for the Pristine 8.6+ high pH drinking water product in Sidoarjo Regency, East Java. This study is Explanatory Research with a quantitative approach using a survey method through the distribution of questionnaires. Explanatory research is intended to explain the causal relationship between research variables and test the formulated hypotheses. The sample consists of 100 respondents with the criteria of being over 17 years old, residing in Sidoarjo City, and being consumers who are currently purchasing or consuming Pristine 8.6+ drinking water. The validity test uses Pearson's Product-Moment correlation formula, while the reliability test uses Cronbach's Alpha. Partial Least Square analysis is used for hypothesis testing in this study. The results show that 1) The product variable influences purchasing decisions for Pristine 8.6+ consumers, 2) Price has a positive influence on purchasing decisions for Pristine 8.6+ drinking water consumers, 3) The place variable does not positively influence purchasing decisions for Pristine 8.6+ drinking water, 4) Promotion has a positive influence on purchasing decisions for Pristine 8.6+ drinking water consumers, 5) There is an influence of the marketing mix on purchasing decisions.